2016
DOI: 10.1136/annrheumdis-2016-209270
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in patients with spondyloarthritis treated with TNF inhibitors: a collaborative study from the ARTIS and DANBIO registers

Abstract: In patients with SpA, treatment with TNFi was not associated with increased risks of cancer, neither overall nor for the six most common cancer types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 31 publications
4
74
0
7
Order By: Relevance
“…While findings from these studies are inconsistent, recent analyses suggest no excess NHL risk related to TNFI use. 8, 9, 14, 18, 20 In a 2011 meta-analysis of observational and prospective registry studies of patients with RA, PsA or AS, no significantly elevated risk was found (pooled risk estimate 1.11, 95% confidence interval (CI) 0.70-1.51). 20 More recently, investigators using the British Society for Rheumatology Biologics Registrar for Rheumatoid Arthritis (BSRBR-RA) concluded that their study “ruled out” the risk of lymphomas in patients with RA for up to 5 years after treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…While findings from these studies are inconsistent, recent analyses suggest no excess NHL risk related to TNFI use. 8, 9, 14, 18, 20 In a 2011 meta-analysis of observational and prospective registry studies of patients with RA, PsA or AS, no significantly elevated risk was found (pooled risk estimate 1.11, 95% confidence interval (CI) 0.70-1.51). 20 More recently, investigators using the British Society for Rheumatology Biologics Registrar for Rheumatoid Arthritis (BSRBR-RA) concluded that their study “ruled out” the risk of lymphomas in patients with RA for up to 5 years after treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…These results are further confirmed by real‐world data from four national biologic registries (ARTIS [Antirheumatic Therapies in Sweden], BIODASER, Corrona RA registries, DANBIO [Danish nationwide registry]), which gathered data of >4600 patients with ankylosing spondylitis treated with TNF inhibitors. All registries demonstrated no increased risk of overall malignancies among TNF inhibitors exposed patients with ankylosing spondylitis compared to both the general population and patients with ankylosing spondylitis without TNF inhibitor treatment . No increased risk was reported for specific site cancers, including lymphoma, nonmelanoma skin cancer, and melanoma .…”
Section: Malignanciesmentioning
confidence: 95%
“…All registries demonstrated no increased risk of overall malignancies among TNF inhibitors exposed patients with ankylosing spondylitis compared to both the general population and patients with ankylosing spondylitis without TNF inhibitor treatment . No increased risk was reported for specific site cancers, including lymphoma, nonmelanoma skin cancer, and melanoma . Altogether, data on malignancy risk after TNF inhibitors in patients with ankylosing spondylitis is solid enough to reassure patients with ankylosing spondylitis and their physicians considering TNF inhibitors treatment.…”
Section: Malignanciesmentioning
confidence: 96%
See 1 more Smart Citation
“…International collaborations between registries, including Swedish QRs, have provided useful data (3,4). However, pooling individual-level data from registries located in different countries often raises problems of legal as well as logistic nature that may necessitate specific considerations (5,6).…”
Section: Introductionmentioning
confidence: 99%